Charcoal Heart - Ali, Mahmoud; Adil, Amina; Sawlani, Rahul; Jeffreys, Sana; Cheema, Omar; Galazka, Patrycja; Tajik, A. Jamil (JACC. Case reports, 2021)
A 59-year-old woman with history of skin melanoma and complete excision presented with palpitations. Transthoracic echocardiogram revealed right atrial mass attached to interatrial septum. Cardiac magnetic resonance was suggestive of metastatic melanoma. Laboratory tests revealed elevated liver enzymes. Liver ultrasonography showed a large mass positive for metastatic melanoma by biopsy. (Level of Difficulty: Intermediate.) [Display omitted]